Баруун Монголын сэргэсэн орогений геодинамикын байдал - Ж., Бямба; Д., Эрдэнэчимэг (Geological Issues, 2022)
During the Devonian orogeny in Western Mongolia, the continental crust was formed and this area became gradually flattened during the Permian period, which was part of the process of the formation of the supercontinent Pangaea. At this time, the westsouth continuation of the Paleotethys Sea closed from the east side and was closed from the Middle Triassic due to the collision of the Tarim craton massif and At this time, the west-south continuation of the Paleotethys Sea closed from the east side and was closed from the Middle Triassic due to the collision of the Tarim craton massif and the Caledonian-Hercynian fold rim on the west-south side of the Siberian craton. Because of this, the district was experiencing a mid-slab uplift regime. From the 2nd half of the Triassic, the fluctuating movement of the upper crust began to become active in the level of uplift of the Mongolian Altai plate, and the orogeny process began to intensify again in the Mongolian Altai district, which had a flat surface. Subsequently, the development of the recovered mountains began at the end of the Cretaceous period.